Acute Invasive Fulminant Fungal Rhinosinusitis: An Evaluation of 25 Cases - Eroğlu, Ergin; Pamuk, A.Erim; Özer, Serdar (ENT Updates, 2024)
Background: Acute invasive fungal rhinosinusitis (AIFRS) is a severe infection that affects the nasal cavity and paranasal sinuses, often seen in individuals with comorbidities such as diabetes mellitus and hemato-oncological diseases. This study aims to retrospectively analyze patients diagnosed with AIFRS from 2014 to 2023. Methods: The study was a single-center, descriptive investigation focusing on demographic details, clinical presentation, radio-pathological features, and suggested management of AIFRS patients. Results: Of the 25 patients involved in the study, with a mean age of 48 years, hematooncological diseases were the most common underlying condition (44%), followed by diabetes mellitus (28%). Fungal analysis revealed Aspergillus species (32%) and Mucor (24%). The most frequently involved site was the middle turbinate (84%), while the least affected was the inferior turbinate (36%). The mortality rate was 48%, primarily due to underlying hemato-oncological diseases (32%). Aspergillus (16%) and Mucor (16%) were the most commonly encountered pathogens in fatal cases. Conclusion: Patients with diabetes mellitus, hemato-oncological diseases, or secondary immunodefciency undergoing steroid treatment should be vigilantly screened for AIFRS. Early diagnosis and prompt management are crucial to improve patient outcomes.